Increasing of the Biogas Release During the Cattle Manure Fermentation by Means of the Rational Addition of Substandard Flour as a Cosubstrate - Polishсhuk, V.M.; Shvorov, S.A.; Tarasenko, S.Ye.; Antypov, I.O. (Наука та інновації, 2020)
Introduction. The processing of livestock waste and agricultural production enables not only improving environmental safety, but also obtaining energy resources. Problem Statement. Cow manure is used to produce biogas, but its yield is relatively low. One way to increase biogas yield is the joint fermentation of cow manure with substandard flour, which cannot be used as human food and as feed for farm animals. However, the flour content in the substrate, at which the biogas yield is maximum and there is no inhibition of the methane fermentation process, is not a solved issue. Purpose. Increase biogas yield by adding substandard flour to a cow manure-based substrate. Materials and Methods. Research of biogas yield during methane fermentation of substrate based on cow manure with the addition of substandard flour was carried out on a biogas plant consisting of a methane tank with a working volume of 30 l and wet gasholder at periodic substrate loading and fermentation temperature 35 °C. The portion of the substrate included 1.7 kg of manure, 2.5 kg of water and 50, 100, 250 or 500 g of flour. The composition of flour in the substrate was 1.2%, 2.3%, 5.6% and 10.6%. The dichotomy method was used to determine the optimal flour content in the substrate, provided the maximum biogas yield. Results. The maximum biomethane release is 14.3 l/kg dry organic matter (DOM), at 1.2% of the flour content in the substrate; 20.9 l/kg DOM, at 2.3%; 19.2 l/kg DOM, at 5.6%. At a content of 10.6% flour in the substrate, the biogas did not burn, fermentation quickly stopped. The optimum flour content in the substrate based on cow manure, in which the biogas yield increases 1.5 times, is 3.7%. Conclusions. Based on the conducted experimental studies, a model of biogas yield with gradual loading of the substrate was built and the optimal flour content in the substrate was determined, at which the maximum biogas yield is provided.